Influence on seed quality parameters under different temperature and artificial ageing treatment in cumin (Cuminum cyminum) - TRIVEDI, VRUSHANK; RAO, KALYAN; SASIDHARAN, N; PATEL, D A (The Indian Journal of Agricultural Sciences, 2023)
The experiment was conducted in the Department of Seed Science and Technology, B A College of Agriculture, Anand Agricultural University, Anand to know the influence on seed quality parameters under different temperature and artificial ageing treatment in cumin (Cuminum cyminum L.). Two varieties were tested for seed quality, viz. Gujarat Cumin 1 (GC 1) and Gujarat Cumin 4 (GC 4). The laboratory experiment was laid out in completely randomized design (factorial concept) with four temperature treatments (10oC, 15oC, 20oC and 25oC) and three repetitions. The artificial ageing experiment consisted of three ageing treatments (0 day, 3 days and 5 days) with four repetitions. The experiment results revealed that, the different temperature regimes showed significant effect on seed germination and other quality parameters in cumin genotypes. The GC-1 interacting with 20oC was higher for different quality parameters like first count (45.66%), final count (94%), seedling length (9.33 cm), seedling fresh weight (219.66 mg), seedling dry weight (10.76 mg), seedling vigour index I (877) and seedling vigour index II (93). In seed ageing experiment, the different days of artificial ageing also showed significant effect on the seed viability and longevity. GC-1 recorded higher germination (55.50%), seedling length (3.45 cm), seedling dry weight (27.57 mg), vigour index –I (192) and vigour index –II (1539) as compared to GC-4 at the end of five days ageing period.